2007
DOI: 10.1111/j.1365-3083.2007.02047.x
|View full text |Cite
|
Sign up to set email alerts
|

Naturally Acquired Immunity and Reduced Susceptibility to falciparum Malaria in Two Subpopulations of Endemic Eastern India

Abstract: This study was aimed to assess the prevalence of naturally acquired humoral immune responses and their association with reduced susceptibility to malaria in children and adults with differential clinical conditions from an Indian zone where malaria is endemic. The study was undertaken in an eastern province of India (Keonjhar, Orissa) in a group of 341 children (both younger and older) and 98 adults living in two different areas, Town area and Forest area. They were studied for their parasitological and immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 25 publications
3
13
0
Order By: Relevance
“…The higher growth-inhibitory activity of the Malian total IgG is likely due to anti-malarial antibodies with specificities other than AMA1. The data suggest that Malians with high levels of anti-AMA1 antibodies are likely to have high levels of antibodies to other malarial antigens, as has been reported in other epidemiological studies (30, 31), and as a consequence, the total IgG with higher anti-AMA1 ELISA units showed higher growth-inhibitory activity in vitro.…”
Section: Discussionsupporting
confidence: 78%
“…The higher growth-inhibitory activity of the Malian total IgG is likely due to anti-malarial antibodies with specificities other than AMA1. The data suggest that Malians with high levels of anti-AMA1 antibodies are likely to have high levels of antibodies to other malarial antigens, as has been reported in other epidemiological studies (30, 31), and as a consequence, the total IgG with higher anti-AMA1 ELISA units showed higher growth-inhibitory activity in vitro.…”
Section: Discussionsupporting
confidence: 78%
“…For example, the presence of local parasite population structure has been suggested to be a factor of exposure-related immunity, identifiable through seroprevalence frequencies to various P. falciparum surface antigens. However, the evidence for this remains somewhat controversial, as populations located in close proximity were reported to be more related (Biswas et al, 2008), in contrast identical genetic structures were also found between two distant localities ( i.e ., eastern and northeastern India) (Joshi et al, 2007). Previous work has shown an association between genetic diversity of the pfcrt -haplotypes and variable transmission intensities throughout India (Mallick et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Children aged up to 15 years had higher risk for clinical malaria disease when compared to adults over 15 years. The higher risk of experiencing a clinical malaria episode among children is possibly be due to the naturally under-developed humoral immune responses to different stage-specific antigens of P. Falciparum otherwise acquired with age [29]. In this study in an endemic area, high cumulative parasite count was associated with lower risk of getting a new clinical malaria episode suggesting that increased exposure to malaria parasites with time may result into protective effect to future clinical malaria episodes.…”
Section: Discussionmentioning
confidence: 74%